PENGARUH LATIHAN PASSING BAWAH BERPASANGAN TERHADAP KETERAMPILAN PASSING BAWAH DALAM PERMAINAN BOLA VOLI PADA SISWI YANG MENGIKUTI EKSTRAKURIKULER DI SMK NEGERI 1 PANGKALAN LESUNG - Asep Riadi; Aref Vai; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The aim of this study is to find out the effectsof paired bump pass training on bump pass skill in volleyball for The female students Who took on extracurricular activities at SMA Negeri 1 pangkalan lesung. This study was conducted by applying an experimental method with "One-Group pre-test post-test design" as the research design. The population of this study were 16 students Who took on extracurricular activities at SMK Negeri 1 pangkalan lesung. The instrument used in this study was bump pass skill in a minute. Data analysis and hypothesis test was using the t-test with a significant level (α) of 0.05 with a confidence level of 0.95%. Based on data analysis with the results: Pre-test average 17.69 on Posttest 24.44 with results (tcount 6.88> ttable 1.753), ha was accepted. Therefore, it can be concluded that paired bump pass training was affecting on bump pass skills in volleyball for female students Who took extracurricular activities in SMK N 1 pangkalan lesung.Key Words: Down Passing, Extracurricular Students, volleyball.